Biosynthesis of food constituents: Amino acids: 4. Non-protein amino acids - a review - Jan Velíšek; Roman Kubec; Karel Cejpek (Czech Journal of Food Sciences, 2006)
This review article gives a brief survey of the principal pathways that lead to the biosynthesis of the most important non-protein amino acids occurring in foods and feeds. These amino acids have been divided into the following groups: 3-amino acids and 4-amino acids, N-substituted amino acids, alicyclic amino acids, hydroxyamino acids, sulfur-containing amino acids, basic amino acids, and taurine.